Real-world implications of QT prolongation in patients receiving voriconazole and amiodarone. (8th October 2018) - Mourad, Ahmad; Stiber, Jonathan A; Perfect, John R; Johnson, Melissa D
Abstract: Objectives: Voriconazole, a triazole antifungal, is frequently prescribed in a complex patient population with comorbidities that require concomitant administration of QT interval-prolonging medications. We sought to evaluate QT interval prolongation in patients receiving concomitant therapy with voriconazole and amiodarone and to assess the development of any potentially fatal cardiac arrhythmias as a result. Methods: We conducted a retrospective observational study of patients who had received amiodarone and voriconazole concomitantly between 2005 and 2015, with a prior period of monotherapy, who had ECG data during monotherapy (baseline) and concomitant therapy (follow-up). Results: We included 46 patients in our final analysis. Overall, the mean change in QT corrected (QTc) from baseline to follow-up was 49.0 ms ( P  <   0.001). Eighteen (39.1%) patients had a follow-up QTc interval ≥500 ms, with 17 (37.0%) having a change in QTc interval ≥60 ms from baseline to follow-up. Men were more likely to have a follow-up QTc interval of ≥500 ms. In multivariate analysis, only low serum potassium concentration and concomitant 'possible' QT-prolonging drugs were associated with a follow-up QTc interval ≥500 ms and a lower baseline QTc interval was associated with a change in QTc interval of ≥60 ms. Discharge diagnoses of cardiac arrhythmias and events were assessed and none was found to be related to concomitant therapy. Conclusions: Concomitant therapy with amiodarone and voriconazole significantly prolonged the QTc interval to a degree greater than that on monotherapy. However, no clinically significant cardiac events were observed.